Between conviction and uncertainty : philosophical guidelines for the practicing psychotherapist - Downing, Jerry N., 1943- (SUNY series, alternatives in psychology., 2000)
"At a time when scores of seemingly incompatible theories and methods are competing for ascendancy in psychotherapy, one could argue that the crucial intellectual and moral dilemmas of this field are largely philosophical in nature. Yet most psychotherapists are never formally exposed to philosophical thinking during their training years or subsequent careers. Between Conviction and Uncertainty: Philosophical Guidelines for the Practicing Psychotherapist makes a significant contribution by bridging this gap. Jerry Downing examines and clarifies the philosophical context - epistemological, scientific, moral - within which psychotherapy functions. He demonstrates the necessity of maintaining a creative tension - a dialectic - between conviction and uncertainty in the work of the therapist and, more importantly, he explores in depth how this might be done. Further, he presents these sometimes complex ideas in prose that is truly reader-friendly. This book should appeal to all practitioners, supervisors, and students/trainees who find value in reflecting on the nature of psychotherapeutic practice, as well as to readers with theoretical or philosophical interests in psychotherapy."--Jacket